Functional Differences between Human NKp44− and NKp44+ RORC+ Innate Lymphoid Cells - Hoorweg, Kerim; Cornelissen, Ferry; Aparicio-Domingo, Patricia; Papazian, Natalie; Kazemier, Geert; Spits, Hergen; Cupedo, Tom (Frontiers in Immunology, 2012)
Human RORC+ lymphoid tissue inducer cells are part of a rapidly expanding family of innate lymphoid cells (ILC) that participate in innate and adaptive immune responses as well as in lymphoid tissue (re) modeling. The assessment of a potential role for innate lymphocyte-derived cytokines in human homeostasis and disease is hampered by a poor characterization of RORC+ innate cell subsets and a lack of knowledge on the distribution of these cells in adults. Here we show that functionally distinct subsets of human RORC+ innate lymphoid cells are enriched for secretion of IL-17a or IL-22. Both subsets have an activated phenotype and can be distinguished based on the presence or absence of the natural cytotoxicity receptor NKp44. NKp44+ IL-22 producing cells are present in tonsils while NKp44− IL-17a producing cells are present in fetal developing lymph nodes. Development of human intestinal NKp44+ ILC is a programmed event that is independent of bacterial colonization and these cells colonize the fetal intestine during the first trimester. In the adult intestine, NKp44+ ILC are the main ILC subset producing IL-22. NKp44− ILC remain present throughout adulthood in peripheral non-inflamed lymph nodes as resting, non-cytokine producing cells. However, upon stimulation lymph node ILC can swiftly initiate cytokine transcription suggesting that secondary human lymphoid organs may function as a reservoir for innate lymphoid cells capable of participating in inflammatory responses.